2015
DOI: 10.1523/jneurosci.3279-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Microglial Process Convergence Toward Neuronal Dendrites by Extracellular Calcium

Abstract: Extracellular calcium concentrations in the brain fluctuate during neuronal activities and may affect the behavior of brain cells. Microglia are highly dynamic immune cells of the brain. However, the effects of extracellular calcium concentrations on microglial dynamics have not been investigated. Here, we addressed this question in mouse brain slices and in vivo using two-photon microscopy. We serendipitously found that extracellular calcium reduction induced microglial processes to converge at distinct sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
96
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 39 publications
6
96
0
Order By: Relevance
“…This process involves the activation of neuronal NMDA receptors, calcium influx, subsequent ATP release, and the activation of P2Y 12 receptors (Eyo et al, 2014). A similar phenomenon, described recently and termed microglial process convergence (MPC) involves the convergence of microglial processes on neuronal dendrites in response to a reduction of extracellular Ca 2þ (Eyo et al, 2015). The induction of microglial migration, morphological transformation and process extension towards various pathological signals by P2Y 12 receptors probably represents a protective mechanism which could be beneficial during early stages of injury.…”
Section: The Role Of P2y Receptors In Neuroinflammationmentioning
confidence: 89%
“…This process involves the activation of neuronal NMDA receptors, calcium influx, subsequent ATP release, and the activation of P2Y 12 receptors (Eyo et al, 2014). A similar phenomenon, described recently and termed microglial process convergence (MPC) involves the convergence of microglial processes on neuronal dendrites in response to a reduction of extracellular Ca 2þ (Eyo et al, 2015). The induction of microglial migration, morphological transformation and process extension towards various pathological signals by P2Y 12 receptors probably represents a protective mechanism which could be beneficial during early stages of injury.…”
Section: The Role Of P2y Receptors In Neuroinflammationmentioning
confidence: 89%
“…Visual deprivation reduced microglial process motility, which was reversed after light-reexposure. Evo et al [22*] observed that microglial processes converge at dendritic spines in mouse brain slices in response to reduced extracellular calcium. They describe this phenomenon as “microglial process convergence”, which is apparently mediated by purinergic signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Microglia-neuronal contact alters with changes in neuronal input. In P2Y12 receptor (P2Y12R) knock-out mice, microglial process convergence towards neuronal dendrites was eliminated [22*]. Tatsumi et al [30] recently show that microglial P2Y12R signaling following nerve injury involves downstream Rho-associated protein kinase (ROCK) that acts at actin.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations